Poverty, Growth, and Inequality in Sub-Saharan Africa : Did the Walk Match the Talk under the PRSP Approach? - Sembene, Daouda (IMF Working Papers; Working Paper ;, 2015)
Poverty Reduction Strategy Paper (PRSP) countries in Sub-Saharan Africa have shown strong signs of growth resilience in the aftermath of the recent global crisis. Yet, this paper finds evidence that growth has more than proportionately benefited the top quintile during PRSP implementation. It finds that PRSP implementation has neither reduced poverty headcount nor raised the income share of the poorest quintile in Sub-Saharan Africa. While countries in other regions have been more successful in reducing poverty and increasing the income share of the poor, there is no conclusive evidence that PRSP implementation has played a role in shaping these outcomes.